Identification of Factors Affecting the Productivity of Medium Small Micro Enterprises (MSMEs) - Danang Indrajaya; Rifqi Humaidi Assiddiqqi Nasution; Leli Deswindi (Yayasan Riset dan Pengembangan Intelektual, 2022)
Economic growth in Indonesia tends to increase because the contribution of MSME growth to GDP is quite large. MSMEs contributed 7,009,283 (in billion rupiah) or equivalent to 59.84% of total GDP in 2016 and in 2017 GDP growth reached 7,704,635.9 (in billion rupiah) or equivalent to 60% of total GDP in Indonesia with a market share absorption of 99%. This study uses a Multiple Criteria Decision Making (MCDM) approach by combining 2 methods, namely the Decision Making Trial and Evaluation Laboratory (DEMATEL) and the Fuzzy Analytic Network Process (FANP). This study supports 3 types of MSME categories based on the standards of the Indonesian Muslim Women Entrepreneurs' Organization (WPMI), namely Basic, Advance and Professional. The results of the application of the Super Decision application to the business environment cluster show that the financial support sub-cluster is a major factor in the productivity of MSMEs at the Basic and Advance levels. Meanwhile, at the Professional level, Regulations and Business Boundaries are the main factors. In the Human Resources cluster, the sub-cluster experience is the main factor at the Basic level. Meanwhile, the education sub-cluster is the main factor at the Advance and Professional levels. In the Production Resources cluster, the marketing distribution sub-cluster is the main factor at the Basic level. Meanwhile, the raw material management sub-cluster is a major factor.